2008
DOI: 10.1097/ijg.0b013e318163bdd1
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Quality of Life in Patients With Glaucoma: A Cross-sectional Analysis Using the Geriatric Depression Scale-15, Assessment of Function Related to Vision, and the Glaucoma Quality of Life-15

Abstract: Depression is more common in patients with increasing glaucoma severity (age, 70 to 79 y). In patients with glaucoma or ocular hypertension, age and GQL-15 summary score are independent risk factors for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 14 publications
14
121
2
4
Order By: Relevance
“…Depressive disorders were the second leading cause of YLD according to Global Burden of Disease Study 2010 (Ferrari et al 2013) as it was in the Japanese Clinical study (Mabuchi et al 2012). The range of the prevalence of depression in glaucoma patients was between 11.4% and 32.1% in the Australian clinical study performed by Skalicky et and Goldberg (Skalicky & Goldberg 2008). …”
Section: Epidemiological Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Depressive disorders were the second leading cause of YLD according to Global Burden of Disease Study 2010 (Ferrari et al 2013) as it was in the Japanese Clinical study (Mabuchi et al 2012). The range of the prevalence of depression in glaucoma patients was between 11.4% and 32.1% in the Australian clinical study performed by Skalicky et and Goldberg (Skalicky & Goldberg 2008). …”
Section: Epidemiological Datamentioning
confidence: 99%
“…Table 1). The severity of glaucoma and older age of the patients, in the study of Skalicky and Goldberg, contributed to higher prevalence of depression in glaucoma patients (Skalicky & Goldberg 2008). The purpose of this study was also to determinate the association of depression and the QoL in glaucoma patients.…”
Section: Depression and Glaucoma -Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Glaucoma patients are at increased risk of depression, especially as HRQOL declines and/or the disease progresses. (Skalicky and Goldberg, 2008;Tastan et al, 2010) Depression has been shown to be associated with nonadherence. (Friedman et al, 2009;Pappa et al, 2006) Pappa et al demonstrated that 42% of glaucoma patients were nonadherent, omitting at least 2 doses per week.…”
Section: Adherence and Persistence Are Vital Elements Of Treatmentmentioning
confidence: 99%